Vývoj operativy onemocnění jater a žlučových cest - Krška, Z; Sváb, J; Ulrych, J (Rozhledy v chirurgii, 2012)
INTRODUCTION: Surgical liver and biliary tract diseases remain to be among the most serious and the incidence of illnesses requiring surgical treatment has been increasing. It is therefore essential to consider the new possibilities of oncological and miniinvasive care, including ablation treatment, and to evaluate their importance and integration in the treatment system. MATERIAL AND METHODS: The article presents a retrospective analysis of three consecutive sets of patients from 1991-2011. Our monitoring focused primarily on bile duct lesions and on primary and secondary tumours of the liver. Assessments included the extent and method of the operation, neoadjuvant and adjuvant care, complications, lethality, and survival rate. RESULTS: Our study confirmed that the number of surgically treated secondary tumours (colorectal carcinoma metastases) rose by 9% as a result of downstaging (i.e., the combination of chemotherapy and oncological treatment or RFA) and the use of embolization via the portal vein and sequential resections. With no fundamental changes recorded in hepatocellular carcinoma treatment, resection or transplantation still appears to be the only curative treatment method. One-year survival is minimal without these procedures. We recorded a slight increase in the incidence of cholangiocarcinoma from 6 to 10.3%. The results of extrahepatic and hepatic form resections range from 0 to 90%, depending on the stage of the disease. Biliary duct lesions are treated more frequently at the time of laparoscopic surgery; they are diagnosed later or when stenosis has already developed, and hepaticojejunoanastomosis is the most widely applied procedure in treating the lesions. The authors indicate the ablation methods in hepatic and bile duct tumour treatment only when resection treatment is not possible. CONCLUSION: Surgical resection treatment in malignant diseases of the liver and biliary tract remains the primary treatment method with a high curative potential. Neoadjuvant combined treatment increases the eligibility of patients for such surgical procedures. In biliary tract lesions, we also regard the surgical approach as dominant. The overview of results for individual periods implies the necessity of interdisciplinary care in order to achieve better results in surgical management.
Keywords: játra; Liver Diseases; nemoci žlučového ústrojí; nemoci jater; Humans; Liver; chirurgie žlučových cest; Biliary Tract Surgical Procedures; lidé; Biliary Tract Diseases